The same but different: Businessmen’s social trajectories in the province of Córdoba, Argentina, 2015-2019 - Schaigorodsky, Emilia (2022)
The article presents the results of the research regarding business elites of the province of Córdoba, Argentina, between 2015 and 2019. Beginning with the discussion of Latin-American and Argentinian research literature, it focuses on the analysis of businessmen’s social trajectories, describing its similarities and building a typology of its differences. The inquiry takes, as a theoretical position, the proposal of Tilly (2000) regarding inequality mechanisms. The research was carried out with a qualitative methodological approach, including multiple techniques (press analysis, observation and biographical interviews). A positional method for the identification of elites was used (Perissinotto and Codato, 2015), for the purpose of constructing social trajectories. The main results paved the way for building four types of trajectories, taking into account two analytical axis: economic activity in relation with the agents’ origin sociabilities; and their ways of political participation within the business communities. These results shed light on the heterogeneity followed by economic elites, and the importance of its understanding in view of inequalities present in Latin-American societies.